Papillary Tumor of the Pineal Region: Clinical Presentations, Prognostic Factors, Treatments, and Outcomes - Nasrollahi, Hamid; Kadkhodaei, Behnam; Hamedi, Seyed Hassan; Ansari, Mansour; Ahmadloo, Niloofar; Mosalaei, Ahmad; Omidvari, Shapour; Mohammadianpanah, Mohammad (Reports of Radiotherapy and Oncology, 2016)
The pineal region is a rare site for primary tumors of the central nervous system. Papillary tumor of the pineal region (PTPR) is a relatively new phenomenon in this region. Considering the rarity of this tumor, the clinical course, treatment, and outcomes are not well studied. In the present study, we searched PubMed for relevant articles. A total of 72 articles were retrieved from PubMed. The exclusion criteria were autopsy and archive series, animal studies, and reports without clinical data. We had no access to the full - text of some articles; accordingly, 19 articles were excluded from the analysis. Data from 53 reports, including 50 case reports and three case series (a total of 73 patients), were collected and analyzed. The patients’ mean age was 33.5 (± 15.4) years. Forty - two cases were male and 31 were female. The most common symptom was headache in patients (80%). Other common symptoms included visual complaints (40%), nausea (31%), memory loss (7%), Parinaud’s syndrome (4%), and impaired gait (2%). Among 73 patients, 32 had undergone complete tumor resection. Twenty - nine patients had received conventional external beam radiotherapy, stereotactic radiosurgery (n, 10), brachytherapy (n, 5), and proton therapy (n, 1). Eight patients received no adjuvant therapy, and data presented in other reports were incomplete. Among the patients (n, 73), 11 received chemotherapy. Fifty patients had no evidence of recurrence at the time of report, while three patients had died. Local recurrence was the most common pattern of relapse (28%); nonetheless, parenchymal and meningeal involvement was also observed. The median disease - free survival (DFS) was 24 months, while five- and ten - year DFS rates were 50.1% and 25.0%, respectively. The median overall survival was 24 months. Generally, PTPR has an indolent course with a tendency towards local recurrence; nonetheless, an aggressive clinical course, associated with parenchymal and meningeal metastases, is well established.